Multimodal method for landslide risk analysis - Pollock, William; Grant, Alex; Wartman, Joseph; Abou-Jaoude, Grace (MethodsX, 2019)
[Display omitted] Quantitative landslide risk analysis is a key step in creating appropriate land use policies. However, regional scale landslide hazard and risk studies are traditionally based on a single, infinite-slope style of failure, belying the differing consequences of a diverse range of failure modes. In this paper we expand an existing multimodal coseismic landslide hazard model to create a method for multimodal, multi-trigger quantitative landslide risk analysis and apply it to the country of Lebanon. •Physics-based, mode-specific models for coseismic and precipitation-induced landslides capture the effects of multiple failure types and triggering scenarios.•A new model for analyzing slope stability against rotational failures allows for efficient, regional scale assessments.•Open-source mapping of built-up area is used to identify elements at risk.